Kritik Terhadap Sistem Ekonomi Kapitalis: Studi UU No 11 Tahun 2020 Tentang Cipta Kerja Perspektif Teori Nilai - Sarah Nur Rahmawati; Afifatul Munawiroh; Bagus Prayogi (Rechtenstudent, 2021)
Even though the Omnibus Law Bill has been enacted into law, there is still controversy in it. There are still many regulations that overlap and are unclear about the workers (the workers). The job creation law further strengthens the position of employers compared to siding with the workers. The regulation of working hours on workers' salaries increasingly shows the current impartiality of the government. This, of course, becomes an alienation for the workers because in their own country they are forced laborers who are hired for inappropriate pay. Borrowing the thought of Karl Marx said that the existence of a most basic alienation occurs in human work. Work should be a form of identity for humans, but now the opposite is happening due to the capitalist system and the exploitation of the means of work. Ironically this is what happened. This paper is based on library research and field research. This research is a qualitative research using a phenomenology approach. The purpose of this paper is to find out the meaning contained in Law No. 11 of 2020 concerning the regulation of working hours for the proletariat. 11 of 2020, in which there are contradictions that favor investors compared to labor workers. It is hoped that this criticism can be heard by policy makers so that there is a balance between the interests of investors and the interests of workers.